Recreational forest landscape planning in Selangor, Malaysia - Hussein, Mohd. Kher; Mohd. Tahir, Osman (Online Journal of Science and Technology (T O J S A T), 2014)
Recreational forest in Peninsular Malaysia has been established by the Forestry Department of Peninsular Malaysia for sustainable use since 1965. The purpose of the establishment is for preservation and conservation as well as wise use of natural resources. Until today, the numbers of recreational forest in Peninsular Malaysia had increased where it was reported that the total sites are 125 as for 2010. In Selangor itself, it was reported that 10 sites had been developed. Nevertheless, their landscape planning is based on adhoc or insitu approach that is unsustainable attitude. Due to that, this study tries to comprehend a stakeholder perception towards recreational forest landscape planning related to planning implementation, development approach, facility development and criteria’s that can pursue to sustainable planning approach. By understanding stakeholder perception, a more sustainable planning approach can be developed for the comfort of users and the environment in the future. Thus, objectives of the study was to analyze stakeholders’ perception towards sustainable recreational forest landscape planning in order to benefited to future development in terms of environment, social and economy. Results shows that stakeholders’ perception is still in line with the statement of landscape recreational forest planning was developed through adhoc approaches that are unsustainable way. This is due to the fact that this site has been developed without landscape master plan, grounded on user demands and requirements. Therefore, a concrete actions need to be taken and landscape master plan should be prepared by the management to overcome the issue of unsustainable landscape development planning.